Use of the electronic nose to monitor the influences of modified atmosphere packaging on the storage of contaminated garlic - Alireza Makarichian; Ebrahim Ahmadi; Reza Amiri Chayjan; Doostmorad Zafari; Seyed Saeid Mohtasebi (Heliyon)
Garlic is a valuable product that has an excessive application due to its impressive nutritional value. The issue of garlic storage as a seasonal product is critical. Therefore, the effective conditions in the storage should be identified and monitored. In this research, three important treatments in garlic storage including packaging materials, packaging atmosphere, and fungal infection were studied. The effect of these treatments on some important qualitative indices in garlic such as weight reduction, browning index, acidity, total soluble solids, toughness, etc was investigated. Also, the non-destructive technology of the electronic nose (E-Nose) was used as a complementary solution in garlic quality monitoring. The data were evaluated by the Analysis of Variance (ANOVA), Principal Component Analysis (PCA), Backpropagation Neural Network (BPNN), Linear Discriminant Analysis (LDA), and Partial Least-Squares Regression (PLSR) methods. The results disclosed well that applying the studied treatments can affect the changes in qualitative traits. Also, changes in qualitative traits were associated with aromatic changes. The E-Nose responses toward the aroma of different treatment combinations (TCs) had a unique pattern but did not represent an exclusive trend. The PLSR results proved among the qualitative properties, the physical and mechanical traits had the highest (97 %) and lowest (24 %) correlation with aroma changes, respectively. Therefore, the E-Nose can be employed as a complementary and non-destructive solution in the quality monitoring of the storage of products such as garlic.